Ultrasound-assisted one-pot synthesis of dihydropyrimid-2-one/thiones catalyzed by zirconyl chloride hexahydrate - Omar Yahya; Badie Ahmed; Imad Thanoon (مجلة التربية والعلم, 2013)
ABSTRACT Different substituted dihydropyrimidinones and  dihydropyrimidin thiones were generated from the Biginelli reaction between aromatic aldehydes, 1,3-dicarbonyl and urea or thiourea under ultrasonic irradiation method. Compared with classical Biginelli reaction ,this method can be depending on selectivity of the suitable catalyst (zirconyl chloride hexahydrate) ,excellent yield ,easy work and short reaction time .The structure of the new compounds were confirmed by physical and available spectroscopic methods .